(untitled) (Al-Academy, 2020)
The value of culture in its interaction is composed and formulated according to compatible and incompatible roles which view the identity that adopts that formation although it is in most cases perceived and declared. The attraction and difference characteristic might be implied within subjective and procedural meaning through which it seeks to make the identity mobile subject to identity- shaping cultural causes implying the conflicts that take the shape and culture of real time. As for the end of the twentieth century and afterward where the concepts of hegemony, globalization, cultural invasion, colonial and imperial culture, all these causes made the cultural identity concept appear on the surface of the critical studies as a title that functions to preserve the identity of nations and peoples and in its turn produces a reaction to an imperial, colonial economic action established by the globalization. Hence the concept of duality of the (ego and the other) stems. The researcher in the content of his study emphasized the shape of the cultural identity and the role and problem of the ego and the other, and intended to specialize in the Iraqi theatre for these repercussions and what the theatrical text produced. The researcher used the script of the play Rainy Night a model for his research in all its mythological, social, economic and political levels that formulate the cultural identity.